Factors Affecting Quality of Life of Aged Diabetics - Phooripoom, Chamras (Journal of Health Science of Thailand, 2018)
The purpose of this cross-sectional analytical research was to study the level of the quality oflife and the factors that had effects on aged diabetic patients. The sample group consisted of 80patients who received treatment at Diabetic Clinic, OPD Trat Hospital. Data collection was done by using 2 interview forms. The first form was to gather informationconcerning population demographic factor, economic and social factor. The second form was aboutthe quality of life according to the concept proposed by Zhan. The data was analysed by usingpercentage, mean, standard deviation and correlation tests: chi-square and Fisher’s exact test. Theresults of this research showed that the quality of life of the aged diabetics was found to be good.There were associations at 95% level of significance between the quality of life of the aged diabeticsand the population demographic factors (age and marital status), the economic and social factor(income), and health factors (duration of illness and knowledge ). It is recommended that a health team should be aware of the factors related to health behaviourconcerning the self-care of aged people and applied this awareness to comprehensively look afterdiabetics to enhance the quality of life of aged diabetics or, at least, to maintain it at the same level.